Value added, wages, and labor market flows at the establishment level - Christian Merkl; Heiko Stüber (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2017)
In this paper, we analyze the connection between value added, wages, and labor market ows at the establishment level. For this purpose, we first develop a simple model to illustrate the expected comovement of these variables. For the empirical analysis, we link the new German Administrative Wage and Labor Market Flow Panel (AWFP) dataset to the IAB Establishment Panel survey. We show that establishments' hires rates have a positive and separations rates a negative comovement with establishment-specific value added, whereby hires react by more than separations. Our estimation results point towards inefficient separation behavior in some parts of the economy. In addition, we provide evidence that establishments' partial equilibrium reaction is an important driver for aggregate labor market dynamics.
Keywords: E24; E32; J64; 330; labor market flows; value added; wages; administrative data; establishments